Experimental investigation of phase relations and thermodynamic properties in the system ZrO2–Eu2O3–Al2O3. Issue 6 (May 2016) - Fabrichnaya, O.; Saenko, I.; Kriegel, M.J.; Seidel, J.; Zienert, T.; Savinykh, G.; Schreiber, G.
Abstract: Phase relations in the Eu2 O3 –Al2 O3 and ZrO2 –Eu2 O3 –Al2 O3 systems were studied experimentally using X-ray diffraction (XRD), scanning electron microscopy combined with dispersive X-ray spectrometry (SEM/EDX) and differential thermal analysis (DTA). The stability ranges of Eu4 Al2 O9 phase were established as 1748–2095 K. Peritectic character of Eu4 Al2 O9 melting was confirmed. Temperatures and compositions of eutectic reactions were measured. Heat capacities of EuAlO3 and Eu4 Al2 O9 were measured by differential scanning calorimetry (DSC) in the range 298.15–1400 K. Thermodynamic description of Eu2 O3 –Al2 O3 system has been derived based on own results and data from literature. Isothermal sections of the ZrO2 –Eu2 O3 –Al2 O3 system at temperatures 1523–2073 K were constructed based on experimental study and thermodynamic calculations based on binary extrapolations. Temperatures and compositions of two eutectic reactions were measured. Based on obtained experimental results thermodynamic parameters in the ZrO2 –Eu2 O3 –Al2 O3 system have been optimized using CALPHAD approach.